Using ionic Liquids-Based Surfactant in formulating Nimodipine Polymeric Nanoparticles: A Promising Approach for Improved Performance - M.Rashid, Asmaa; Ghareeb, Mowafaq M. (Iraqi Journal of Pharmaceutical Sciences, 2025)
According to definition, polymeric nanoparticles (NP) exist as tiny, solid, colloidal particles ranging from 1-1000 nm in size, manufactured from biodegradable and biocompatible polymers, lipids, or metals. Polymeric nanoparticles have attracted substantial attention in various fields, including imaging, and diagnostics, and considered as interesting choices for drug delivery and targeting. The synthesis and stabilization of nanoparticles are crucial for their successful application. Ionic Liquids-Based Surfactants (ILBS) have emerged as promising solvents and stabilizers owing to their distinct features, like minimal volatility, high thermal stability, and customizable physicochemical properties. It is distinguished from commercially available surfactants by outstanding features such as low critical micelle concentration (CMC), improved wetting and foaming capabilities, in addition to strong solubilization ability. The present work aimed to formulate polymeric nanoparticles using Ionic Liquids-Based Surfactant (ILBS) 1-tetradecyl-3-methylimmidazolium bromide (TDMB) as a stabilizer to improve Nimodipin’s poor solubility and dissolution rate. They were produced using the nanoprecipitation method. Results show that most of the prepared NID-PNP formulations exhibited particle sizes in the nanoscale range. The optimized formula (F5), stabilized with ionic liquid 0.5% and soloplus prepared under a stirring speed of 1000 rpm, exhibited a particle size (64.33nm) and PDI (0.067). Moreover, it displayed an enhanced dissolution rate in phosphate buffer pH 7.4 with 96% within 10 minutes, compared to the pure NID 15.4 % in the identical media. Collectively, NID-PNP significantly enhanced the solubility and dissolution velocity of NID and offered an encouraging nano platform for hydrophobic drug delivery